2018
DOI: 10.3389/fnmol.2018.00368
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Morphology, Function and Homeostasis Are Impaired by Expression of an N-terminal Calpain Cleavage Fragment of Ataxin-3

Abstract: Alterations in mitochondrial morphology and function have been linked to neurodegenerative diseases, including Parkinson disease, Alzheimer disease and Huntington disease. Metabolic defects, resulting from dysfunctional mitochondria, have been reported in patients and respective animal models of all those diseases. Spinocerebellar Ataxia Type 3 (SCA3), another neurodegenerative disorder, also presents with metabolic defects and loss of body weight in early disease stages although the possible role of mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…3, A and B). Even more interesting, a fragment of ataxin-3, which was recently described to cause mitochondrial dysfunction (47), was highly enriched in the nucleus as well ( Fig. 3C).…”
Section: Physiological Function Of Ataxin-3mentioning
confidence: 80%
See 1 more Smart Citation
“…3, A and B). Even more interesting, a fragment of ataxin-3, which was recently described to cause mitochondrial dysfunction (47), was highly enriched in the nucleus as well ( Fig. 3C).…”
Section: Physiological Function Of Ataxin-3mentioning
confidence: 80%
“…This is of special interest, as it was previously reported that cleavage of mutant ataxin-3 leads to a nuclear translocation of the polyQcontaining fragment (4,9). At the same time, these fragments are considered to be more toxic and show an increased propensity to form aggregates compared with the full-length protein (2,24,26,27,47,89,90). Ataxin-3 is known to be a deubiquitinating enzyme (7,8), and that cellular turnover of ataxin-3, as well as its steady-state level, is regulated by its catalytic activity (13).…”
Section: Characteristics Of Ataxin-3 Isoformsmentioning
confidence: 98%
“…bioenergy defects and mitochondrial dysfunction can lead to progressive decline of the central nervous system, and can even lead to endogenous apoptosis of neurons 16,18. Parkinson's disease may occur when the same pathological changes occur in dopaminergic cells in the substantia nigra.…”
mentioning
confidence: 99%
“…bioenergy defects and mitochondrial dysfunction can lead to progressive decline of the central nervous system, and can even lead to endogenous apoptosis of neurons 16,18. The link between mitochondrial defects and the risk of neurodegenerative diseases may lay the foundation for individualized therapeutic interventions for future neurodegenerative disorders 18,19. The link between mitochondrial defects and the risk of neurodegenerative diseases may lay the foundation for individualized therapeutic interventions for future neurodegenerative disorders 18,19.…”
mentioning
confidence: 99%
See 1 more Smart Citation